Eco-environmental construction in the YanŽgou watershed of the Loess Plateau: models and benefits - Liu, Puling; Xu, Yan'gou; Söderlund, Leif; Tian, Junliang; Ju,Tongjun; Xu, Xuexuan (MTT, 2005)
This paper discusses the processes of eco-system recovery, including the construction models and measures for vegetation rehabilitation introduced in the YanŽgou watershed since 1998. The socio-economic and ecoenvironmental benefits achieved during the period of reconstruction are analysed. The results indicate that the arrangement of comprehensive controlling measures and the selection of eco-agriculture construction models in the YanŽgou watershed were appropriate. The watershed provides scientific evidence and a demonstrative example of the construction of eco-agriculture in the Loess Plateau.
Keywords: Ys; Kiina; luonnonmukainen maataloustuotanto; Yan gou watershed; eco-agriculture; construction models; ecological benefit